Pengembangan Media Manipulatif Papan Abce Pada Materi Luas Permukaan Bangun Ruang Sisi Datar - 'Aniqoh, Lazatin; Qohar, Abd; M. Husen Al Farisy (Journal of Mathematics Education and Science, 2025)
Junior high school students often struggle to understand mathematical concepts. Observations of classroom learning indicate that many students find it difficult to grasp mathematical ideas when there is no tangible representation of those concepts. One such challenge lies in understanding the surface area of three-dimensional geometric shapes with flat faces. Students’ academic performance is also influenced by their interest in the learning process and the tools used. This study aims to develop a manipulative learning media called the "ABCe Board," designed to assist students in discovering the concept of surface area in solid shapes with flat faces. The development of this media followed the ADDIE model. Data collection and analysis techniques were conducted on a limited scale. The research subjects consisted of 18 students from SMP Ar-Rohmah Putri, focusing on the topic of surface area of solid figures. Validity analysis by experts indicated that the media met the criteria for validity, with an average score of 3.4. Meanwhile, practicality analysis based on student responses showed that the media was considered practical, with an average score of 3.39. The media is recommended for use in mathematics instruction to help students understand the concept of surface area more concretely.